Using animation to assist learning - Hasnan, Mazliana; Abu Hashim, Anis Hasliza; Alias, Asmidar (Universiti Teknologi MARA, 2009)
Many educators nowadays use animation to help learners understand their studies better especially in the area that learners find difficult. Animations can be produced much easier and faster in the form of high-quality computer generated with the advancement in computer technology. Previous research showed that the incorporation of animation, text, pictures and sound could enhance learners' achievement and motivate the interest in learning. The main objective of this paper is to discuss the use of animation to support teaching and learning. Both educators and learners could benefit from this technology.